Recommendations to reduce inequalities for LGBT people facing advanced illness: ACCESSCare national qualitative interview study. (January 2018) - Bristowe, Katherine; Hodson, Matthew; Wee, Bee; Almack, Kathryn; Johnson, Katherine; Daveson, Barbara A; Koffman, Jonathan; McEnhill, Linda; Harding, Richard
Background: Lesbian, gay, bisexual and/or trans (LGBT) people have higher risk of certain life-limiting illnesses and unmet needs in advanced illness and bereavement. ACCESSCare is the first national study to examine in depth the experiences of LGBT people facing advanced illness. Aim: To explore health-care experiences of LGBT people facing advanced illness to elicit views regarding sharing identity (sexual orientation/gender history), accessing services, discrimination/exclusion and best-practice examples. Design: Semi-structured in-depth qualitative interviews analysed using thematic analysis. Setting/participants: In total, 40 LGBT people from across the United Kingdom facing advanced illness: cancer ( n = 21), non-cancer ( n = 16) and both a cancer and a non-cancer conditions ( n = 3). Results: In total, five main themes emerged: (1) person-centred care needs that may require additional/different consideration for LGBT people (including different social support structures and additional legal concerns), (2) service level or interactional (created in the consultation) barriers/stressors (including heteronormative assumptions and homophobic/transphobic behaviours), (3) invisible barriers/stressors (including the historical context of pathology/criminalisation, fears and experiences of discrimination) and (4) service level or interactional facilitators (including acknowledging and including partners in critical discussions). These all shape (5) individuals' preferences for disclosing identity. Prior experiences of discrimination or violence, in response to disclosure, were carried into future care interactions and heightened with the frailty of advanced illness. Conclusion: Despite recent legislative change, experiences of discrimination and exclusion in health care persist for LGBT people. Ten recommendations, for health-care professionals and services/institutions, are made from the data. These are simple, low cost and offer potential gains in access to, and outcomes of, care for LGBT people.